Molecular simulation studies of MDEA absorption process for CO2 capture - Wai Kean, Sin (2015)
Concentration of CO2 in the earth is gradually increasing every year due to the increased energy use by an expanding economy and population, and an overall growth in emissions come from electricity generation and transportation. Since CO2 is a greenhouse gas, it will trap the heat inside the earth from reflecting back to the outer space and consequently contribute to global warming. So, methyldiethanolamine (MDEA) absorption for CO2 capture process is developed to combat this trend due to its relatively high capacity, a low vapor pressure and small enthalpy of reaction with acid gases. Therefore, a research of studying methyldiethanolamine (MDEA) absorption process for CO2 capture through simulation is developed so that the intermolecular interaction between the solvent (MDEA) and the acid gas (CO2) during the absorption process can be investigated. Through the simulation, the optimum temperature of the carbon dioxide absorption will be determined. Molecular dynamic (MD) simulation will be used to study the interaction of molecule and give an insight on CO2 absorption process. To perform the molecular dynamic (MD) simulation two boxes of carbon dioxide gas and MDEA solvent will combine to study the absorption process. Moreover, thermodynamic condition under NVE, NPT and NVT will be set and the simulation results will be interpreted in terms of radical distribution function. Mean square displacement (MSD) is then used to determine the diffusivity of molecules. MD simulation is performed at temperature of 40°C and 45°C to observe the potential interaction of molecules. Binary system studies the solubility of MDEA in water. Tertiary system studies the potential interaction of CO2 in MDEA solution. It can be concluded that the molecular dynamic simulation clearly shows the potential interaction of molecules and its behaviour.